Isaac Syri Sermones (cód. Plut.89 Sup.96 da BML): edição e glossário - Vanessa Oliveira Silva Gama (2023)
This thesis consists of a paleographic edition, accompanied by a glossary, of the work Isaac Syri Sermones, present in cod. Plut.89 Sup.96 from the Medicea Laurenziana Library. The introduction justifies the importance of editing the work in question; in chapter 1 data about the life, work and doctrine of Isaac of Nineveh are presented; in chapter 2 are introduced the codicological and paleographic descriptions of the manuscript; in chapter 3 there is the paleographic edition of the text, preceded by the justification for choosing the type of edition adopted, as well as the norms for its realization; and in chapter 4 an exhaustive glossary of the text is presented, preceded by the description of the criteria for its elaboration. In the final considerations, the contributions of this work are commented.